2008
DOI: 10.1111/j.1349-7006.2008.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients with hepatocellular carcinoma with macroscopic portal vein or inferior vena cava tumor thrombi receiving external‐beam radiation therapy

Abstract: Prognostic factors in patients with hepatocellular carcinoma (HCC) with tumor thrombosis are not well established, especially for those given external-beam radiation therapy (EBRT). Patients (n = 136) with HCC who had portal vein (PV) or inferior vena cava (IVC) tumor thrombus received EBRT between January 1998 and October 2007. Demographic variables, laboratory values, tumor characteristics, and treatment modalities were determined at diagnosis and before EBRT. The total radiation dose ranged from 30 to 60 Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
1
36
3
Order By: Relevance
“…All of these are not unique. So we reviewed patients' characteristics of other similarity designed studies which showed relatively shorter survival periods for non-responders (2,14). Although it is not directly comparable, our study included more patients who received TACE (93%) than the studies of Zeng et al and Kim et al (66 and 59.3%, respectively), and HAI was mentioned only in our study.…”
Section: Jpn J Clin Oncol 2012;42(8) 727mentioning
confidence: 70%
“…All of these are not unique. So we reviewed patients' characteristics of other similarity designed studies which showed relatively shorter survival periods for non-responders (2,14). Although it is not directly comparable, our study included more patients who received TACE (93%) than the studies of Zeng et al and Kim et al (66 and 59.3%, respectively), and HAI was mentioned only in our study.…”
Section: Jpn J Clin Oncol 2012;42(8) 727mentioning
confidence: 70%
“…Many studies have shown that radiotherapy is an effective treatment for intermediate/advanced HCC, especially when transarterial chemoembolization cannot induce complete necrosis of HCC tumors [22,23], when tumor thrombosis is present in the portal vein or inferior vena cava [24,25], or when abdominal lymph node metastasis is present [26]. In the present study, we analyzed serum VEGF and urine MMP-2 and MMP-9 levels before and after radiotherapy in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, PVTT is sensitive to RT, and the response rate ranges from 25% to 61.5% [52,[55][56][57][58]. Furthermore, RT can boost the treatment responses of tumors and PVTT, and thus likely bestows a survival benefit [33,52,[59][60][61][62]. In one retrospective study, preoperative RT induced PVTT necrosis in 8 patients (53.3%), and preoperative RT followed by surgery resulted in better outcomes than surgery alone for HCC with PVTT (5-year survival rate: 34.8% vs. 13.1%, p=0.0359) [61].…”
Section: Concurrent Chemoradiation With Hepatic Arterial Infusion In mentioning
confidence: 99%